INITIATION RESPONSE FEEDBACK (IRF) TECHNIQUE IN CLASSROOM INTERACTION FOR SEVENTH GRADE STUDENTS AT SMP AL-AMJAD MEDAN - Fidia Laraswati Saragih; Yeni Erlita; Rafika Dewi Nasution (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aims to analyze the types of IRF (Initiation-Response-Feedback) technique that used by the teacher and students in classroom interaction based on Sinclair and Coulthard Technique for seventh grade students at SMP Al-Amjad Medan. The data were collected for two meetings/weeks 2x40 minutes. There were 32 students for seven grade that had research and collected data through observation, audio, and video recording, transcription and interview. This study found that there were four structures of IRF technique in categories teacher those were ; to inform (21.98%), to direct (9.92%), to elicit (29.78%), to check (4.96%), and there were two structures of IRF technique in categories students, those were; to inform (7.09%), to elicit (26,24%). And the most dominant structure of IRF were teacher elicit (IR) (29,78%) and student elicit  (IR) (26,24). The most dominant structure of IRF is teacher elicit (IRF) that produced by the teacher who is expected to create classroom interaction. The reason of the most dominant structured occurred in classroom interaction because the teacher always stimulated the students by questioning and ordering. This study is expected to be an inspiration for other researchers to conduct more conductive research in the future about Initiation Response Feedback (IRF) technique in classroom interaction.   Keywords: Initiation Response Feedback (IRF), Classroom Interaction, Speaking.